Pemaknaan Cover Majalah Tempo “Wajah Kusam Kampus” Edisi 1-7 Februari 2021 - Nur Alfi Laili; Imam Safi'i (Busyro : Jurnal Dakwah dan Komunikasi Islam, 2021)
: Mass media is one of the things that cannot be separated from people's lives. Mass communication media is the latest communication media that is simultaneous, addressed to a number of audiences through online and print media, where messages from an information can be received simultaneously and at the same time. Magazines are general communication tools that are published regularly. one of the characteristics of the magazine is the cover of the magazine. The cover plays a very important role in giving the reader a first impression, because on the cover there are elements of images, symbols, and signs. Charles Sanders Peirce stated that semiotics is another name for logic, namely the formal doctrine of signs. The sign or image on a cover must have a meaning contained in it. To find out the meaning in it, a qualitative research method was used with the cover object of Tempo Face Kusam Kampus as the research material. The meaning contained in the cover of the magazine is that due to the many rectors who are proven to have committed acts of plagiarism, the campus face becomes dirty and flawed.